2016
DOI: 10.1080/01900692.2015.1057852
|View full text |Cite
|
Sign up to set email alerts
|

Social Impact Bonds: Blockbuster or Flash in a Pan?

Abstract: Despite the general hype, Social Impact Bonds’ (SIB) rate of adoption is still modest. The mismatch between widespread interest and actual adoption raises interesting questions as to whether we are still in the early adoption phase of SIBs and massive diffusion is yet to come, or we are observing a marginal phenomenon. In order to shed some light on this issue, the paper provides a review of the cases in which the SIB model has been already applied, exploring the specific configuration employed, with the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 19 publications
0
64
0
6
Order By: Relevance
“…The latter model consists of an intermediary organization which obtains the operating funds, and contracts the service provider. Arena et al (2016) found that the reference model differs from most other SIBs. For instance, risks are often shared between stakeholders instead of transferred to the investor(s).…”
Section: Social Impact Bond As Collaborative Governancementioning
confidence: 98%
See 2 more Smart Citations
“…The latter model consists of an intermediary organization which obtains the operating funds, and contracts the service provider. Arena et al (2016) found that the reference model differs from most other SIBs. For instance, risks are often shared between stakeholders instead of transferred to the investor(s).…”
Section: Social Impact Bond As Collaborative Governancementioning
confidence: 98%
“…There is no blueprint of an SIB configuration (Arena et al 2016). Generally speaking, however, most SIBs include (1) a public sector organization (e.g.…”
Section: Social Impact Bond As Collaborative Governancementioning
confidence: 99%
See 1 more Smart Citation
“…SIBs come in many variations (Arena et al 2016;Clifford and Jung 2016) and are known by different names in different locations: The term "Social Impact Bond" is mostly used in the UK, "Pay for Success" is the common term in the USA, the term "Social Benefit Bond" is used in Australia. Yet all of those forms of funding share certain commonalities: they involve a contract between a commissioner, who is almost invariably a government, and a commissioning agency.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has mostly been in the form of evaluation reports, with only a few academic studies (Arena et al 2016;Cooper et al 2016;Edmiston and Nicholls 2017) analysing existing SIBs with empirical methods. The conceptual arguments concerning SIBs have been following distinctive narratives (Fraser et al 2016): A public-sector-reform narrative located within broader theories of Public Management, a private-financial-sector-reform narrative located within broader theories of social entrepreneurship, and a cautionary narrative sceptical of new public management and social entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%